Analysis of Cutting Tool Modification Effect toward Force, Power and Temperature at Cutting of Material St 42 - Dwijana, I Gusti Komang (Jurnal Energi Dan Manufaktur, 2012)
Until now, research by using of a standard cutting tool at lathe process is still become a subject of many studies in order to reduce of the force, cutting power and temperature. However, there are no satisfactory results yet as expected. In order to participate in overcoming these problems, it is conducted a study on the cutting process by using of standard cutting tool which is modified become double-edged chisel cutting tool. Variables selected in the machining process are cutting speed, feed and depth of pieces motion, due to these variables influence the change in style, cutting power and temperature will be researched. Research procedure was conducted by measuring the amount of cutting force, machining power and cutting temperature in each process multiple pieces of lathe with double-edged chisel cutting tool and then compared with using cutting tool standard. Data collected use of the data acquisition system so that the results obtained can be directly read on a computer screen. The statistical testing to be done is using a procedure paired-samples T test to determine whether use of double-edged chisel cutting tool (modified) will be better when compared with using of standard cutting tool. The result of research show that by use of double-edged chisel cutting tool can be obtained lower of the force, cutting power and temperature.
Keywords: Cutting speed, Feed motion, Depth of cut, Double-edged chisel cutting tool, Style cut, Power machining, Cutting temperature